ANALISIS MEDICATION ERROR FASE PRESCRIBING DAN DISPENSING DI INSTALASI FARMASI RUMAH SAKIT UMUM PUSAT RATATOTOK BUYAT KABUPATEN MINAHASA TENGGARA - Nurjana Usman; Gayatri Citraningtyas; Jainer Pasca Siampa (UNIVERSITAS SAM RATULANGI, 2023)
Medication error is an incident causing drawbacks to patients which, in fact, can be prevented, hence, analysis of medication error in the phases of prescribing (prescription errors) and dispensing (preparing and combining drugs error) was conducted. This study aimed to discover the factors instigating medication error and its percentage in prescribing and dispensing phases. This research employed descriptive analysis in which data was gathered prospectively. Sample was collected through purposive sampling method. 218 pages prescription of outpatients of Internal Poly were recorded at pharmacy installation of Ratatotok Buyat Central General Hospital in Southeast Minahasa Regency. Study finding in prescribing phase included no doctor signature 4.58%, no concentration/dosage 2.75%, no issue date 10.55%, no age/date of birth of patients 30.27%. Meanwhile, dispensing phase only included error in eticket/label 0.91%. Based on the data above, it could be concluded that medication error in prescribing and dispensing phases at Ratatotok Buyat Central General Hospital in Southeast Minahasa Regency occurred.Â Keywords: medication error, prescribing, dispensing, Pharmacy Installation of RSUP Ratatotok Buyat.